Soft-tissue amyloidoma with associated plasmacytoma - Bibhas Saha Dalal; Piyabi Sarkar; Namrata Maity; Sayed Mahmood Nadeem (Wolters Kluwer Medknow Publications, 2016)
Soft tissue amyloidoma with features similar to plasmacytoma, in absence of systemic amyloidosis, is an extremely rare finding. We hereby report the case of a 77 year old man who presented with a painless, nodular swelling on chest wall, diagnosed as soft tissue amyloidoma with plasma cell infiltration. Congo red staining was done to prove the presence of amyloid which showed characteristic "apple-green" birefringence on polarized microscopy. The plasma cells were monoclonal in origin as demonstrated by serum protein and immunofixation electrophoresis. To the best of our knowledge, this is the second such reported case. However close follow up is required, as this patient may develop multiple myeloma in future.